2012
DOI: 10.1093/aob/mcs148
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin is required for the formation of tension wood and stem gravitropism in Acacia mangium seedlings

Abstract: The results suggest that gibberellin plays an important role at the initial stages of formation of tension wood and in stem gravitropism in A. mangium seedlings in response to a gravitational stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…The formation of tension wood on the side upper of the stem occurs to support the gravity of woody angiosperms 26 . When self-weight exceeds the tension, the branches weep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of tension wood on the side upper of the stem occurs to support the gravity of woody angiosperms 26 . When self-weight exceeds the tension, the branches weep.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that GA function in gravitropic responses, although GA1 asymmetry does not trigger gravitropic responses 25 . Nugroho et al 26 suggested that GA has a strong influence on the initial stages during the formation of tension wood and stem gravitropism in Acacia mangium. In peach, the pl phenotype may be associated with GA signaling and upright branch internodes are shorter than those of weeping branches in peach, implying that the upright type may have a lower GA content 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Auxin has been suggested as a key factor for not only cambial meristem maintenance, but also xylogenesis (Aloni et al ., ; Mattsson et al ., ; Moyle et al ., ; Ruzicka et al ., ; Sundberg and Little, ; Uggla et al ., ). GAs are also known to be involved in wood formation (Digby and Wareing, ; Eriksson et al ., ; Israelsson et al ., , ; Little and Pharis, ; Nugroho et al ., ; Wareing, ). Elevated levels of GAs by the overexpression of either AtGA20ox1 or AtGA20ox2 induce an increase in the number of lignified vessels, xylem fibres and increased xylem fibre length in tobacco and poplar (Biemelt et al ., ; Israelsson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic approaches showed that the endogenous ethylene produced in leaning trees acts as a key regulator of the asymmetrical cambial growth in Populus TW [ 9 ]. Recent work also reported that the formation of TW and stem gravitropism in Acacia mangium seedlings requires gibberellins [ 10 ].…”
Section: Introductionmentioning
confidence: 99%